Physicochemical characterisation of barley malts available for the Argentine craft beer industry - Ortega, Marta (2023)
Fil: Ortega, Marta. Universidad Tecnológica Nacional. Facultad Regional de Rosario. Centro de Investigación y Desarrollo en Tecnología de Alimentos; Argentina.